De outros ratos e outras humanidades: uma etnografia das relações entre ratos e humanos nas aldeias Guarani-Mbya no Jaraguá (São Paulo/SP) - Silva Santos, Bruno (2021)
The presence of companion and domestic animals in the daily life of Amerindian societies has been described and analyzed by a growing anthropological bibliography, and also aroused the interest of ethnologists working with the Guarani people. These works highlight the central role of animals in hunting practices, mythological narratives, cosmological categories and in the production of personhood in the Guarani-Mbya society. In contrast, there is scant information and discussion about the so-called commensal or synanthropic creatures, such as small rodents (rats), which coexist with the Guarani-Mbya people. This is a matter as crucial as it is neglected by anthropologists, considering that many indigenous villages, such as the villages in the Jaraguá Indigenous Land (São Paulo/SP), are close to urban and peri-urban areas – where rats are, as we know, a crowd. In this sense, the aim of this dissertation is to present an ethnography about the relations between the Guarani-Mbya people and commensal rats in the Jaraguá Indigenous Land, and to understand the way in which this people perceive, know, classify and relate to these beings. This work is particularly dedicated to understand the relations between rats, indigenous and non-indigenous through the sharp Guarani-Mbya criticism toward the whites’ way of living – which is described both in relation to my interlocutors' distrust of the epidemiology of zoonosis, and from the indigenous criticism toward the predatory potential of urban-industrial society. At the end, I argued that such indigenous criticism can be understood in relation with some Amerindian cosmological categories and mythical themes – showing how, from the Guarani-Mbya point of view, other rats and other humans inhabit big cities.